IMPLEMENTASI PROGRAM DESA MAJU INHIL JAYA DI KECAMATAN TELUK BELENGKONG KABUPATEN INDRAGIRI HILIR - jurnalmap map; Legiman ÔÇÄ; Indra Prasetyo; Sri Mulyani (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
The purpose of this study is to describe the implementation of community empowerment programs in development towards independent villages; and knowing the factors that influence the implementation of community empowerment programs in the development towards Maju Indragiri Hilir Jaya Village in Teluk Belengkong District, Indragiri Hilir Regency. The research uses an approach approach with a research focus on the implementation of community empowerment programs in development towards independent villages consisting of planning, organizational actors, preparation of budget support, community participation and program results and obstacles and efforts to overcome obstacles in implementing community empowerment programs in development towards independent village in Teluk Belengkong District, Indragiri Hilir Regency. Research informants were selected purposively by involving nine key figures. The results showed that the implementation of community empowerment in the implementation of the Indragiri Hilir Jaya Maju Village Program which was carried out in Teluk Belengkong District required self-development, direct assistance, capacity building for human resources, and the development of programs that were socialized for the purpose of village self-reliance in an effort to raise the spirit of community self-help cooperation.